Effect of controlled release of HGF on extracellular vesicle secretion by urine-derived stem cells - Alwan, Abdelrahman; Khalil, Fatma; Bowlby, Joshua; Peko, Gabrielle; Estrada, Exel Valle; Singh, Sangeeta; Deep, Gagan; Zhang, Yuanyuan; Farney, Alan C.; Opara, Emmanuel C. (Frontiers in Bioengineering and Biotechnology, 2024)
Introduction The hepatic growth factor (HGF) stimulates DNA synthesis and cell proliferation and plays a role in tissue protection and regeneration. In this study, we have examined the effect of incubation of HGF with urine-derived stem cells (USCs) on the secretion of small extracellular vesicles (sEV) by the cells. Materials and Methods HGF in the incubation medium was either a bolus administration or a controlled release of an equivalent amount from microbeads within the size range of 50–200 µm made with ultrapurified low-viscosity high-guluronic acid (UP-LVG) alginate. USCs were incubated with or without HGF for 3 days or 7 days before removal of the incubation media, followed by harvesting sEV by the precipitation method. The protein content of isolated sEV was measured by bicinchoninic acid assay (BCA) for these three groups: control (no HGF beads), bolus HGF, and HGF beads. We also performed nanoparticle tracking analysis (NTA), Western blot assay, and ELISA for the HGF content of samples. Results We found a significantly higher concentration of proteins in the HGF microbead group (control release group) compared to the bolus group and the control group after 7 days (p < 0.0017). The NTA data aligned with the BCA; they showed a significantly higher concentration of particles within the size range of sEV (<200 nm) in the group treated with HGF beads compared to the two other groups on day 7 (p < 0.0001). Conclusion We found that administration of HGF to USCs by controlled release of the growth factor significantly enhances the levels of sEV secretion during 7 days of incubation.